Carbon material, negative electrode, and secondary battery
Patent Information
- Application Number
- CN202580023513.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-29
- Filing Date
- 2025-03-28
- Publication Date
- 2026-11-03
AI Technical Summary
Existing negative electrode materials for lithium-ion secondary batteries are easily damaged when used at high densities, leading to a decrease in initial efficiency and a large amount of oil absorption, which in turn reduces energy density.
By controlling the flaxseed oil absorption of carbon materials within a specific range and by rationally controlling the particle size distribution, including adjusting the particle size distribution width and frequency ratio, a combination of carbon materials with different particle sizes is formed, thereby improving the material's high density and filling capacity.
This approach achieves high density of anode materials, reduces compression load, minimizes irreversible capacity increase, and improves initial efficiency and energy density.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to carbon materials, negative electrodes, and secondary batteries. Background Technology
[0002] In recent years, with the miniaturization of electronic devices, the demand for high-capacity rechargeable batteries has gradually increased. In particular, rechargeable batteries with higher energy density and superior charge-discharge characteristics, especially lithium-ion batteries, have attracted attention compared to nickel-cadmium and nickel-metal hydride batteries. As lithium-ion rechargeable batteries, non-aqueous lithium rechargeable batteries have been developed, consisting of positive and negative electrodes capable of absorbing / releasing lithium ions, and a non-aqueous electrolyte containing dissolved lithium salts such as LiPF6 and LiBF4, and have been put into practical use.
[0003] In the past, extensive research has been conducted on improving the performance of lithium-ion secondary batteries, but in recent years, there has been a demand for further improvements in performance. For example, Patent Document 1 discloses a negative electrode material that controls the pore volume and the peak value of the voids within the particles per unit coating ratio.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 2021-158044
[0007] Patent Document 2: Japanese Patent Application Publication No. 2021-158043 Summary of the Invention
[0008] The problem the invention aims to solve
[0009] According to the researchers' findings, the negative electrode material for non-aqueous secondary batteries described in Patent Document 1 has a low tap density, resulting in a large pressing load during plate pressing, which damages the negative electrode material and leads to a decrease in initial efficiency. Furthermore, the negative electrode material disclosed in Patent Document 2 is damaged during pressing when used at high density, causing a decrease in the initial efficiency of the secondary battery. Moreover, the negative electrode material for non-aqueous secondary batteries described in Patent Document 1 has a high oil absorption rate. In batteries where the electrolyte and negative electrode material are mixed to form the electrode, such as semi-solid-state batteries, the amount of electrolyte required to form the electrode increases, leading to a decrease in energy density, making it unsuitable.
[0010] This invention was made in view of the following problems. The object of this invention is to reduce the pressing load during plate pressing and mitigate damage to the negative electrode material by increasing the density of the negative electrode material. This suppresses irreversible capacity increase caused by damage and provides a carbon material with excellent initial negative electrode efficiency. Furthermore, the object is to provide a carbon material for semi-solid-state batteries that reduces oil absorption and achieves high energy density.
[0011] Solution for solving the problem
[0012] There are two independent methods to increase the density of anode materials: increasing the density of the particles themselves; and increasing the density of the powder through particle size distribution control.
[0013] The inventors conducted repeated and in-depth research to understand the above problems, and found that by appropriately combining the above methods and using carbon materials with an oil absorption capacity of flaxseed oil below a specific value, the above problems can be solved, thus completing the present invention.
[0014] Scheme 1 of the present invention is a carbon material, wherein the flaxseed oil absorption is less than 40.0 mL / 100 g, and the frequency q (d50) of the particle size (hereinafter also referred to as d50) when the cumulative volume ratio in the particle size distribution on a volume basis is 50% is less than 13.0%.
[0015] Scheme 2 of the present invention is a carbon material according to Scheme 1, wherein the carbon material comprises a first carbon material and a second carbon material with different d50, and the d50 of the first carbon material is 25 μm or more.
[0016] Scheme 3 of the present invention is a carbon material according to Scheme 1 or 2, wherein the carbon material comprises a first carbon material and a second carbon material with different d50, and the d50 of the second carbon material is less than 15 μm.
[0017] Scheme 4 of the present invention is a carbon material according to any one of Schemes 1 to 3, wherein the carbon material is graphite coated with amorphous material.
[0018] Scheme 5 of the present invention is a carbon material according to any one of Schemes 1 to 4, wherein the difference (d90-d50) between the particle size (hereinafter also referred to as d90) and d50 of the carbon material when the cumulative volume ratio is 90% is 13.0 μm or more.
[0019] Scheme 6 of the present invention is a carbon material according to any one of Schemes 1 to 5, wherein the difference (d50-d10) between the d50 of the carbon material and the particle size (hereinafter also referred to as d10) when the cumulative volume ratio is 10% is 7.0 μm or more.
[0020] Scheme 7 of the present invention is a carbon material according to any one of Schemes 1 to 6, wherein the difference between d90 and d10 of the carbon material (d90-d10) is 20 μm or more.
[0021] Solution 8 of the present invention is a carbon material according to any one of Solutions 1 to 7, wherein the ratio of the difference between d90 and d10 to d50 of the carbon material {(d90-d10) / d50} is 1.05 or more.
[0022] Solution 9 of the present invention is a carbon material according to any one of Solutions 1 to 8, wherein the ratio of the frequency q(d50) of d50 in the volume-based particle size distribution of the carbon material to the frequency q(d25) of the particle size (hereinafter also referred to as d25) when the cumulative volume ratio in the volume-based particle size distribution is 25% (q(d50) / q(d25)) is 3.5 or less.
[0023] Solution 10 of the present invention is a carbon material according to any one of solutions 1 to 9, wherein the ratio (q(d50) / q(d90)) of the frequency q(d50) of d50 in the volume-based particle size distribution of the carbon material to the frequency q(d90) of d90 in the volume-based particle size distribution is 2.0 or less.
[0024] Scheme 11 of the present invention is a carbon material according to any one of Schemes 1 to 10, wherein the frequency q (d25) of d25 in the volume-based particle size distribution of the carbon material is 9.0% or less.
[0025] Scheme 12 of the present invention is a carbon material according to any one of Schemes 1 to 11, wherein the ratio of the frequency q(d90) of d90 to the frequency q(d10) of d10 in the volume-based particle size distribution of the carbon material (q(d90) / q(d10)) is 1.55 or more.
[0026] Scheme 13 of the present invention is a negative electrode, which includes a current collector and an active material layer formed on the current collector, the active material layer comprising any one of Schemes 1 to 12.
[0027] Scheme 14 of the present invention is a secondary battery comprising a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode is a negative electrode comprising any one of Schemes 1 to 12.
[0028] Invention Effects
[0029] The anode using the carbon material of this invention exhibits excellent initial efficiency and long-term storage recovery rate. Detailed Implementation
[0030] The present invention will now be described in detail, but these are merely examples of a preferred embodiment and not specific to it.
[0031] The “~” in the numerical range indicates the range including the values before and after it. For example, “0 mass%~100 mass%” means the range of more than 0 mass% and less than 100 mass%.
[0032] The numerical ranges such as "A to B", "A and above", and "B and below" disclosed in this specification allow for the arbitrary selection of their upper and lower limits.
[0033] "A or above" means "A and / or greater than A", and the numerical range of "greater than A" is also disclosed. Similarly, "below B" means "B and / or less than B", and the numerical range of "less than B" is also disclosed.
[0034] "dn" refers to the particle size when the cumulative volume ratio of all particles is n%. For example, "d10" means that 10% of the total volume is below this particle size. "d50" means that 50% of the total volume is below this particle size, also known as "average particle size".
[0035] q(dn) refers to the frequency of particles with a diameter of dn in the particle size distribution. For example, q(d50) refers to the frequency of particles with a diameter of d50. dn and q(dn) can be calculated from the particle size distribution.
[0036] [Carbon materials]
[0037] Examples of carbon materials used in this embodiment include those with a flaxseed oil absorption capacity of 40.0 mL / 100g or less and a d50 frequency q (d50) of 13.0% or less in the volume-based particle size distribution. If the flaxseed oil absorption capacity is 40.0 mL / 100g or less, it can be used as a high-energy battery even in batteries where the electrolyte and negative electrode material are mixed to form the electrode, such as clay batteries. In this specification, such a carbon material is also referred to as "carbon material (X)".
[0038] In this specification, the linseed oil absorption of the carbon material is a value determined according to ISO 4546.
[0039] Specifically, using an oil absorption measuring device (model name "S410D", developed by Asahi Shimbun Co., Ltd.), 30g of sample was added, and the measurement was performed under the conditions of a flaxseed oil dripping rate of 4mL / min and a rotation speed of 200rpm. The amount of oil absorbed was defined as the amount added when the torque reached 70% of the maximum torque.
[0040] The flaxseed oil absorption of the carbon material is preferably less than 37.0 mL / 100g, more preferably less than 35.0 mL / 100g, and even more preferably less than 33 mL / 100g.
[0041] From the viewpoint of high density, the carbon material (X) in this embodiment is preferably in powder form.
[0042] In this embodiment, the q(d50) of the carbon material (X) is 13.0% or less, preferably 12.5% or less, more preferably 12.0% or less, even more preferably 10.0% or less, and particularly preferably 8.0% or less. By controlling q(d50) within the above range, the number of d50 particles is reduced, the ratio of large to small particles is optimized, and thus the filling performance is improved.
[0043] The volume-based average particle size (d50) of the carbon material (X) in this embodiment is preferably 1 to 50 μm, more preferably 4 to 30 μm, and even more preferably 10 to 25 μm. Here, from the perspective of preventing irreversible capacity increase and initial battery capacity loss, the volume-based average particle size of the carbon material is preferably 1 μm or more, more preferably 4 μm or more, and even more preferably 10 μm or more. Furthermore, from the perspective of suppressing process defects such as scratches during electrode manufacturing and possessing excellent fast charge / discharge characteristics and low-temperature input / output characteristics, the volume-based average particle size of the carbon material is preferably 50 μm or less, more preferably 30 μm or less, and even more preferably 25 μm or less.
[0044] As a method for increasing the density of carbon materials (X), means and specific methods for controlling the particle size distribution to the following state can be listed. One or more means may be used in the methods shown below.
[0045] As a first method, means of expanding the particle size distribution width can be listed. Specifically, methods of controlling at least one of the difference between d90 and d50 (d90-d50), the difference between d50 and d10 (d50-d10), and the difference between d90 and d10 (d90-d10) can be listed as follows.
[0046] The d90-d50 of the carbon material (X) is preferably 13.0 μm or more, more preferably 15.0 μm or more, more preferably 17.0 μm or more, more preferably 19.0 μm or more, more preferably 21.0 μm or more, and more preferably 23.0 μm or more. Furthermore, the d90-d50 of the carbon material (X) is preferably 30.0 μm or less. That is, d90-d50 is preferably 13.0 μm or more and 30.0 μm or less. By controlling d90-d50 within the above range, a larger particle size range can be ensured, making it easier for small particles to enter their gaps and improving filling efficiency.
[0047] The d50-d10 of the carbon material (X) is preferably 7.0 μm or more, more preferably 9.0 μm or more, more preferably 11.0 μm or more, more preferably 13.0 μm or more, more preferably 15.0 μm or more, more preferably 15.5 μm or more, more preferably 16.0 μm or more, and more preferably 16.5 μm or more. Furthermore, the d50-d10 of the carbon material (X) is preferably 25.0 μm or less. That is, d50-d10 is preferably 7.0 μm or more and 25.0 μm or less. By controlling d50-d10 within the above range, the diversity of small particles can be increased, thereby enabling efficient filling of the gaps between large particles.
[0048] The d90-d10 of the carbon material (X) is preferably 20 μm or more, more preferably 25 μm or more, more preferably 30 μm or more, more preferably 35 μm or more, and more preferably 40 μm or more. Furthermore, the d90-d10 of the carbon material (X) is preferably 50 μm or less. That is, d90-d10 is preferably 20 μm or more and 50 μm or less. By controlling d90-d10 within the above range, a wide particle size distribution makes it easier for particles to combine without gaps.
[0049] The ratio of the difference between d90 and d10 of the carbon material (X) to d50, {(d90-d10) / d50}, is preferably 1.05 or more, more preferably 1.15 or more, more preferably 1.20 or more, more preferably 1.30 or more, more preferably 1.40 or more, more preferably 1.50 or more, and more preferably 1.60 or more. Furthermore, the ratio of the difference between d90 and d10 of the carbon material (X) to d50, {(d90-d10) / d50}, is preferably 2.50 or less, more preferably 2.30 or less, and even more preferably 2.10 or less. That is, {(d90-d10) / d50} is preferably 1.05 or more and 2.50 or less. By controlling (d90-d10) / d50 within the above range, the overall particle size distribution can be relatively increased while adjusting the balance of particle sizes, thereby improving the filling rate.
[0050] As a second method, means of reducing the frequency of intermediate particles can be listed. Specifically, in addition to the methods of controlling q(d50) mentioned above, methods of controlling at least one of the following can be listed: the ratio of the frequency q(d50) of d50 in the particle size distribution of the volume reference to the frequency q(d25) of d25 in the particle size distribution of the volume reference (q(d50) / q(d25)), and the ratio of the frequency q(d50) of d50 in the particle size distribution of the volume reference to the frequency q(d90) of d90 in the particle size distribution of the volume reference (q(d50) / q(d90)).
[0051] The q(d50) / q(d25) ratio of the carbon material (X) is preferably 3.5 or less, more preferably 3.0 or less, more preferably 2.5 or less, and even more preferably 2.0 or less. Furthermore, the q(d50) / q(d25) ratio of the carbon material (X) is preferably 1.0 or more, more preferably 1.2 or more, and even more preferably 1.5 or more. That is, the q(d50) / q(d25) ratio is preferably 1.0 or more and 3.5 or less. By controlling the q(d50) / q(d25) ratio within the above range, the proportion of d50 is reduced, and a balance is achieved with the d25 particles, thereby contributing to an increase in density.
[0052] The q(d50) / q(d90) ratio of the carbon material (X) is preferably 2.0 or less, more preferably 1.8 or less, more preferably 1.6 or less, and even more preferably 1.4 or less. Furthermore, the q(d50) / q(d90) ratio of the carbon material (X) is preferably 1.0 or more, more preferably 1.2 or more. That is, the q(d50) / q(d90) ratio is preferably 1.0 or more and 2.0 or less. By controlling the q(d50) / q(d90) ratio within the above range, since large particles (d90) form gaps, if the proportion of d50 is suppressed in order to fill these gaps, it is possible to increase the density.
[0053] As a third method, means of reducing the frequency of small particles can be listed. Specifically, a method can be listed that controls at least one of the following: the ratio of the frequency q(d25) of d25 in the particle size distribution of the volume reference and the frequency q(d90) of d90 in the particle size distribution of the volume reference to the frequency q(d10) of d10 in the particle size distribution of the volume reference (q(d90) / q(d10)).
[0054] The q(d25) of the carbon material (X) is preferably 9.0% or less, more preferably 7.0% or less, and even more preferably 5.0% or less. Furthermore, the q(d25) of the carbon material (X) is preferably 1.0% or more. That is, q(d25) is preferably 1.0% or more and 9.0% or less. By controlling q(d25) within the above range, since fine particles tend to aggregate and increase porosity, suppressing it to an appropriate level helps to increase density.
[0055] The q(d90) / q(d10) ratio of the carbon material (X) is preferably 1.55 or more, more preferably 1.75 or more, and even more preferably 1.95 or more. Furthermore, the q(d90) / q(d10) ratio of the carbon material (X) is preferably 3.0 or less. The q(d90) / q(d10) ratio is preferably 1.55 or more and 3.0 or less. By controlling the q(d90) / q(d10) ratio within the above range, if there are too many small particles, they are prone to agglomeration and a decrease in filling rate; therefore, increasing the proportion of large particles helps to improve the density.
[0056] In this embodiment, the carbon material is preferably 1.26 g / cm³. 3 The above carbon materials were tested to achieve a tap density of 1.26 g / cm³. 3 In summary, when carbon materials are made into negative electrode sheets, the compression load is reduced, which can suppress the irreversible capacity increase caused by damage to the negative electrode material during compression, thus tending to have excellent initial efficiency.
[0057] The tap density of the carbon material is more preferably 1.27 g / cm³. 3 The above is further optimized to 1.28 g / cm³. 3 The above, especially preferred, is 1.29 g / cm³. 3 above.
[0058] In this manual, tap density is the density measured using a tap density measuring device (model name "GeoPyc1365", manufactured by Micromeritics) by applying a compressive force of 108 N.
[0059] From the viewpoint of increasing design freedom, the carbon material (X) in this embodiment preferably includes a first carbon material and a second carbon material with different volume-based average particle size (hereinafter also referred to as d50).
[0060] From the viewpoint of high density, the d50 of the first carbon material is preferably 25 μm or more, more preferably 26 μm or more, and even more preferably 27 μm or more.
[0061] From the viewpoint of high density, the d50 of the second carbon material is preferably 15 μm or less, more preferably 13 μm or less, and even more preferably 11 μm or less.
[0062] In this specification, the volume reference average particle size (d50) is the value of the median diameter of the volume reference measured using a laser diffraction / scattering particle size distribution measuring device.
[0063] Specifically, 0.01 g of sample was suspended in 10 mL of 0.2% by mass aqueous solution of polyoxyethylene sorbitan monolaurate as a surfactant, introduced into a laser diffraction / scattering particle size distribution measuring device, and irradiated with 28 kHz ultrasound at an output power of 60 W for 1 minute. The median particle size of the volume reference in the measuring device was then measured.
[0064] The carbon material (X) in this embodiment preferably includes the first carbon material and the second carbon material described above.
[0065] In the case where the carbon material (X) in this embodiment includes a first carbon material and a second carbon material, in order to increase the density of the carbon material (X), the mass ratio of the first carbon material to the second carbon material (first carbon material: second carbon material) is preferably 9:1 to 5:5, and more preferably 8:2 to 6:4.
[0066] The content of the first carbon material in 100% by mass of carbon material (X) is preferably 40-90% by mass, more preferably 45-85% by mass, and even more preferably 55-75% by mass. Here, from the viewpoint of suppressing electrode expansion to a low level, the content of the first carbon material in 100% by mass of carbon material (X) is preferably 40% by mass or more, more preferably 45% by mass or more, and even more preferably 55% by mass or more. Furthermore, from the viewpoint of maintaining a high initial efficiency of the secondary battery, the content of the first carbon material is preferably 90% by mass or less, more preferably 85% by mass or less, and even more preferably 75% by mass or less.
[0067] The content of the second carbon material in 100% by mass of carbon material (X) is preferably 10-60% by mass, more preferably 15-55% by mass, and even more preferably 25-45% by mass. Here, from the viewpoint of maintaining a high initial efficiency of the secondary battery, the content of the second carbon material in 100% by mass of carbon material (X) is preferably 10% by mass or more, more preferably 15% by mass or more, and even more preferably 25% by mass or more. Furthermore, from the viewpoint of suppressing electrode expansion to a low level, the content of the second carbon material is preferably 60% by mass or less, more preferably 55% by mass or less, and even more preferably 45% by mass or less.
[0068] In this embodiment, the carbon material (X) may include other substances besides the first carbon material and the second carbon material. Examples of other substances include metals that can be alloyed with lithium, their oxides, and conductive materials.
[0069] Regarding the content of other substances, from the perspective of not impairing the original functions of the first carbon material and the second carbon material, the total content of carbon material (X) is preferably 20% by mass or less, more preferably 10% by mass or less.
[0070] In the case where the carbon material (X) in this embodiment includes a first carbon material and a second carbon material, the ratio Rd50 ([the volume-based average particle size (d50) of the first carbon material to the volume-based average particle size (d50) of the second carbon material] / [the volume-based average particle size (d50) of the first carbon material]) is preferably 0.01 to 1, more preferably 0.05 to 0.8, and even more preferably 0.1 to 0.5.
[0071] If Rd50 is within the aforementioned range, the second carbon material can exist in the gaps between the first carbon materials, or the first carbon material can exist in the gaps between the second carbon materials. As a result, by having the second carbon material surrounding the first carbon material, the second carbon material selectively deforms while the first carbon material maintains its shape, preventing damage during pressing even at high densities, thus achieving both high initial efficiency and low expansion. Furthermore, the volume changes of the first and second carbon materials caused by the absorption / release of lithium ions during charging and discharging are absorbed by the gaps formed between the first and second carbon materials. Therefore, the breakage of conductive pathways caused by the volume changes of the first and second carbon materials can be suppressed, resulting in improved cycle characteristics, fast charge / discharge characteristics, and high capacity.
[0072] For at least one, and preferably all, of the carbon material (X), the first carbon material, and the second carbon material described in this embodiment, the specific surface area (SA) of the carbon material is preferably 0.5 to 10.0 m². 2 / g, more preferably 0.8–6.5m 2 / g, more preferably 1.0–5.0m 2 / g, more preferably 1.0–3.0m 2 / g. Here, considering factors such as ensuring excellent lithium-ion entry / exit sites, rapid charge / discharge characteristics, and low-temperature input / output characteristics, the specific surface area of the carbon material (A) is preferably 0.5 m². 2 / g or more, preferably 0.8m 2 / g or more, further preferably 1.0m 2 / g or more. Furthermore, considering factors such as suppressing side reactions with the electrolyte, preventing a decrease in initial charge / discharge efficiency, increasing gas generation, and improving battery capacity, the specific surface area of the carbon material is preferably 10.0 m². 2 / g or less, more preferably 6.5m 2 / g or less, preferably 5.0m 2 / g or less, more preferably 3.0m 2 / g or less, more preferably 2.0m 2 / g or less. In this embodiment, the carbon material (X), the first carbon material, and the SA of the second carbon material can be the same or different.
[0073] In this specification, the specific surface area (SA) is a value determined by the BET (Brunauer-Emmett-Teller) method.
[0074] Specifically, using a specific surface area measuring device, the sample is pre-depressurized and dried at 350°C for 15 minutes under nitrogen flow, then cooled to liquid nitrogen temperature. A nitrogen-helium mixed gas with the relative pressure of nitrogen to atmospheric pressure precisely adjusted to 0.3 is used to determine the nitrogen adsorption BET single-point method using gas flow.
[0075] In this embodiment, when the carbon material (X) comprises a first carbon material and a second carbon material, the ratio of the specific surface area (SA) of the first carbon material to the specific surface area (SA) of the second carbon material, RSA ([specific surface area (SA) of carbon material (B)] / [specific surface area (SA) of carbon material (A)]), is preferably 0.01 to 100, more preferably 0.1 to 10, and even more preferably 0.2 to 5. Here, the aforementioned ratio RSA is preferably 0.01 or more, more preferably 0.1 or more, and even more preferably 0.2 or more. Furthermore, it is preferably 100 or less, more preferably 10 or less, even more preferably 6 or less, even more preferably 5 or less, and particularly preferably 3 or less.
[0076] If the RSA is within the above range, the lithium-ion input and output are ensured, resulting in excellent fast charge and discharge characteristics, low-temperature input and output characteristics, and suppression of side reactions with the electrolyte. This prevents a decrease in initial charge and discharge efficiency, an increase in gas generation, and an increase in battery capacity.
[0077] The tap density of at least one, preferably both, of the first carbon material and the second carbon material is preferably 1.15–1.40 g / cm³. 3 More preferably, it is 1.17–1.35 g / cm³. 3 More preferably, it is 1.20–1.30 g / cm³. 3 Here, considering factors such as suppressing process defects like scratches during electrode fabrication, improving calendering properties due to increased filler content, facilitating the formation of high-density negative electrode sheets, reducing the tortuosity of the lithium-ion migration path during electrode fabrication, ensuring smooth electrolyte movement due to regular interparticle void shapes, and improving rapid charge / discharge characteristics, the tap density of the carbon material is preferably 1.15 g / cm³. 3 The above, more preferably 1.17 g / cm³ 3 The above is further preferred to be 1.20 g / cm³. 3 The above. Furthermore, considering the appropriate space on the particle surface and inside to prevent particle hardness, excellent electrode compressibility, rapid charge / discharge characteristics, and excellent low-temperature input / output characteristics, the tap density of the carbon material is preferably 1.40 g / cm³. 3 The following is a preferred value: 1.35 g / cm³ 3 The following is a further preferred value of 1.30 g / cm³. 3 The tap densities of the first and second carbon materials can be the same or different.
[0078] From the viewpoint of lithium ion acceptability, at least one, preferably all, of the carbon material (X), the first carbon material, and the second carbon material in this embodiment is preferably graphite coated with amorphous material, and more preferably spheroidized natural graphite coated with amorphous material.
[0079] In this embodiment, at least one, preferably all, of the carbon material (X), the first carbon material, and the second carbon material described above, from the viewpoint of lithium ion acceptability, the mass ratio of spherical graphite particles to amorphous carbonaceous material is preferably 1:0.3 to 1:0.01, more preferably 1:0.2 to 1:0.05. The mass ratio of spherical graphite particles to amorphous carbonaceous material in the carbon material (X), the first carbon material, and the second carbon material of this embodiment may be the same or different.
[0080] In this specification, when the carbon material (X), the first carbon material, and the second carbon material described above are coated with amorphous carbon material or graphitic material, the coating rate of the carbon material based on the amorphous carbon material or graphitic material is also referred to as the coating rate.
[0081] In this embodiment, the coating rate of at least one of the carbon material (X), the first carbon material, and the second carbon material, preferably all of them, is preferably 0.1% to 15%, more preferably 1% to 12%, further preferably 2% to 10%, and even more preferably 3% to 8%. Here, considering the smooth movement of lithium ions from graphite, rapid charge / discharge characteristics, and excellent low-temperature input / output characteristics, the coating rate is preferably 0.1% or more, more preferably 1% or more, further preferably 2% or more, and particularly preferably 3% or more. Furthermore, considering the sufficient graphite proportion and ease of achieving high capacity, the coating rate is preferably 15% or less, more preferably 12% or less, further preferably 10% or less, and particularly preferably 8% or less. The coating rates of the carbon material (X), the first carbon material, and the second carbon material in this embodiment may be the same or different.
[0082] In this specification, the coating percentage (%) is calculated using the following formula (1). That is, it is calculated based on the mixing ratio of graphite with amorphous carbonaceous material or graphitic material and the firing yield after firing.
[0083] Coverage rate (%) = ([mass of the sintered sample - mass of spheroidized natural graphite] / [mass of the sintered sample]) × 100 (1)
[0084] When the above mixing ratio and firing yield are unknown, the coating percentage (%) is estimated using the difference in true density between graphite and amorphous carbonaceous or graphitic materials.
[0085] Specifically, the crystallinity of spheroidized natural graphite in the carbon material (X), the first carbon material, or the second carbon material of this embodiment is confirmed by the d002 value. If the d002 value is 3.357 Å or less and the crystallinity is high, the coating rate (%) is calculated using the following formula (2).
[0086] Coverage (%) = 596.72 - 264.02 × True density (2)
[0087] In this embodiment, at least one, preferably all, of the carbon material (X), the first carbon material, and the second carbon material described above, the theoretical d002 value of graphite is 3.354 Å, and the d002 value of highly crystalline natural graphite is close to the theoretical value.
[0088] In this embodiment, at least one, preferably all, of the carbon material (X), the first carbon material, and the second carbon material described above, considering that graphite has high crystallinity and sufficient charge / discharge capacity, the d002 value of the carbon material is preferably 3.357 Å or less, more preferably 3.356 Å or less, and even more preferably 3.354 Å. The d002 values of the carbon material (X), the first carbon material, and the second carbon material in this embodiment may be the same or different.
[0089] In this embodiment, at least one, preferably all, of the carbon material (X), the first carbon material, and the second carbon material described above, considering that graphite has high crystallinity and sufficient charge / discharge capacity, the Lc of the carbon material is preferably 900 Å or more, more preferably 1000 Å or more. The upper limit of Lc is not particularly limited, but it is generally set at 1000 Å as the upper limit for measurement accuracy. The Lc of the carbon material (X), the first carbon material, and the second carbon material in this embodiment may be the same or different.
[0090] In this specification, d002 is defined as the interplanar spacing of the lattice planes (002 planes) determined by X-ray diffraction using the vibratory method, and Lc is defined as the crystallite size determined by X-ray diffraction using the vibratory method. The X-ray diffraction measurement conditions are as follows.
[0091] Sample: A substance prepared by adding approximately 15% by mass of high-purity X-ray standard silicon powder to the test object and mixing them together.
[0092] X-rays: CuKα rays.
[0093] Measurement range: 20°≤2θ≤30°.
[0094] Step angle: 0.013°.
[0095] Sample adjustment: Fill the recessed part of the sample plate with powder sample to a depth of 0.2 mm to make a flat sample surface.
[0096] In this specification, the true density is a value determined by liquid-phase displacement method (specific gravity bottle method) using butanol. The true density was measured 5 times, and the average value was used.
[0097] In this embodiment, at least one, preferably all, of the carbon material (X), the first carbon material, and the second carbon material described above, considering excellent filling properties and capacity, the true density of the carbon material is preferably 2.200 g / cm³. 3 The above, more preferably 2.210 g / cm³ 3 The above is further preferred to be 2.220 g / cm³. 3 The theoretical true density of graphite is 2.262 g / cm³. 3 In this embodiment, the true densities of the carbon material (X), the first carbon material, and the second carbon material may be the same or different.
[0098] In this embodiment, at least one, preferably all, of the carbon material (X), the first carbon material, and the second carbon material described above, the value obtained by subtracting the tap density from the compressed density of the carbon material is preferably 0.10 to 0.80 g / cm³. 3 More preferably, it is 0.15–0.60 g / cm³. 3 More preferably, it is 0.20–0.40 g / cm³. 3 Here, considering that the particles are not too hard and can be compressed to a high density, the aforementioned difference is preferably 0.10 g / cm³. 3 The above, more preferably 0.15 g / cm³ 3 The above is further preferred to be 0.20 g / cm³. 3 The above. Furthermore, considering that the particles have moderate hardness, will not be excessively crushed even when pressed onto the electrode surface at high density, and that the electrolyte moves smoothly, the aforementioned difference is preferably 0.80 g / cm³. 3 The following is more preferably 0.60 g / cm³. 3 The following is a further preferred value: 0.40 g / cm³ 3 The values obtained by subtracting the tap density from the compressed density of the carbon material (X), the first carbon material, and the second carbon material in this embodiment may be the same or different.
[0099] In this specification, the value obtained by subtracting the tapped density from the compressed density is calculated using the following formula (3). The value obtained by subtracting the tapped density from the compressed density represents the ease of filling under load and can be used as an indicator of particle hardness.
[0100] The value obtained by subtracting the tapped density from the tablet density (g / cm³) 3 = Tablet density - Tap density (3)
[0101] In this specification, the tablet density is a value determined by the following method.
[0102] Two types of clamps were inserted into a mold with an inner diameter of 10mm: a 10mm diameter, 35mm long shaft as a push-in clamp and a 10mm diameter, 6mm long shaft as a receiving clamp. The mold was then placed in a device capable of measuring the load and height during clamping. A load of 15kgf was applied using a hydraulic pump, and the clamp height was measured. Then, only the push-in clamp was removed, 0.6g of carbon material was added, and the push-in clamp was reinserted. The mold was then placed under a hydraulic jack, the pressure valve was tightened, and the pressure was slowly increased to 0.9t / cm². 2 The pressure was rapidly increased to 2.4 t / cm. 2 Afterward, hold for 3 seconds, remove your hand from the hydraulic jack and wait 60 seconds before releasing the pressure valve to depressurize. Then, place the device again in a configuration capable of measuring the load and height during clamping, apply a 15 kgf load using the hydraulic pump, and measure the height of the clamp after pressurization. Simultaneously, measure the mass of the pressurized carbon material, and use the density calculated from the difference in clamp height and mass as the tablet density. The load per unit area is calculated using the hydraulic jack's scale, cylinder diameter, and mold inner diameter.
[0103] In this embodiment, the tablet density of at least one, preferably all, of the carbon material (X), the first carbon material, and the second carbon material described above is preferably 1.30 to 1.79 g / cm³. 3 More preferably, it is 1.40–1.70 g / cm³. 3 Here, the preferred tablet density is 1.30 g / cm³. 3 The above, more preferably 1.40 g / cm³ 3 In addition, the preferred value is 1.79 g / cm³. 3 The preferred value is 1.70 g / cm³. 3 The following applies. In this embodiment, the compression densities of the carbon material (X), the first carbon material, and the second carbon material may be the same or different.
[0104] The sphericity of at least one, preferably all, of the carbon material (X), the first carbon material, and the second carbon material in this embodiment is preferably 0.88 to 0.99, more preferably 0.90 to 0.98, and even more preferably 0.92 to 0.97. Here, from the perspective of reducing lithium-ion diffusion tortuosity, facilitating smooth movement of the electrolyte in the interparticle gaps, and providing excellent fast charge / discharge characteristics, the sphericity of the carbon material is preferably 0.88 or higher, more preferably 0.90 or higher, and even more preferably 0.92 or higher. Furthermore, from the perspective of ensuring good contact between the carbon materials and excellent cycle characteristics, the sphericity of the carbon material is preferably 0.99 or lower, more preferably 0.98 or lower, and even more preferably 0.97 or lower. The sphericity of the carbon material (X), the first carbon material, and the second carbon material in this embodiment may be the same or different.
[0105] In this specification, the roundness is determined by the particle size distribution of the equivalent circle diameter through flow particle image analysis and calculated by the following formula (4).
[0106] Specifically, deionized water was used as the dispersion medium, and polyoxyethylene sorbitan monolaurate was used as the surfactant. The dispersion was obtained by ultrasonic dispersion. Then, the shape of the particles was photographed using a flow-through image analysis device. Based on images obtained from at least 1000 particles, the roundness of particles with an equivalent circular diameter ranging from 1.5 μm to 40 μm was averaged as the roundness.
[0107] [Circularity] = [Circumference of the equivalent circle with the same area as the particle projection shape] / [Actual circumference of the particle projection shape] (4)
[0108] In this embodiment, at least one, preferably all, of the carbon material (X), the first carbon material, and the second carbon material described above, the cumulative pore volume of the carbon material is preferably 0.003 to 0.120 mL / g, more preferably 0.005 to 0.090 mL / g, and even more preferably 0.010 to 0.070 mL / g. From the perspective of moderately easy deformation during pressing, the cumulative pore volume of the carbon material is preferably 0.003 mL / g or more, more preferably 0.005 mL / g or more, and even more preferably 0.010 mL / g or more. Furthermore, it is preferably 0.120 mL / g or less, more preferably 0.090 mL / g or less, and even more preferably 0.070 mL / g or less. The cumulative pore volumes of the carbon material (X), the first carbon material, and the second carbon material in this embodiment may be the same or different.
[0109] (Manufacturing methods for carbon materials)
[0110] The method for manufacturing the carbon material (X) in this embodiment is not particularly limited, but it is preferable to manufacture it in a way that allows the flaxseed oil absorption to be less than 40.0 mL / 100g.
[0111] The first carbon material and the second carbon material can be manufactured separately, or they can be manufactured together.
[0112] For example, a preferred method is to spheroidize carbon material raw materials in the presence of a granulating agent, subject them to pressure treatment, and then attach an amorphous carbon precursor or a graphitic precursor. Specifically, a preferred manufacturing method includes the following steps (1) to (7).
[0113] Process (1): The process of adjusting the particle size of carbon material raw materials.
[0114] Process (2): The process of mixing carbon material raw materials with granulating agent.
[0115] Process (3): The process of spheroidizing carbon material raw materials.
[0116] Process (4): The process of removing the granulating agent.
[0117] Process (5): Pressure treatment process.
[0118] Process (6): The process of adding amorphous carbonaceous or graphitic materials.
[0119] Process (7): The process of mixing multiple carbon materials.
[0120] The following describes the processes (1) to (7), but processes other than those (1) to (7) may be included before and after each process, and the manufacturing method is not limited to those including processes (1) to (7).
[0121] (Process (1))
[0122] Process (1) is the process of adjusting the particle size of carbon material raw materials.
[0123] The raw material for carbon materials is graphite. Considering high crystallinity and excellent capacity, natural graphite and artificial graphite are preferred. Considering even higher crystallinity, even better capacity, and the fact that heat treatment is not required during manufacturing, natural graphite is preferred. Graphite with fewer impurities is preferred, and it is preferable to use graphite after purification treatment as needed.
[0124] (Process (2))
[0125] Process (2) is the process of mixing carbon material raw materials with granulating agent.
[0126] The granulating agent is preferably a liquid when spherizing carbon material raw materials.
[0127] Furthermore, the granulating agent preferably contains an organic compound that becomes amorphous carbon.
[0128] Furthermore, the granulating agent is preferably a granulating agent that does not contain organic solvents, a granulating agent that contains organic solvents and at least one of the organic solvents does not have a flash point, or a granulating agent that contains organic solvents with a flash point of 5°C or higher.
[0129] When the granulating agent meets the above necessary conditions, it becomes a liquid bridge between the carbon material raw materials during the spheroidization process. The capillary negative pressure of the liquid bridge and the surface tension of the liquid generate attraction between the carbon material raw materials, which can effectively shorten the distance between the carbon material raw materials.
[0130] (Process (3))
[0131] Process (3) is a process of spheroidizing carbon material raw materials.
[0132] By spherizing the carbon material raw material, it exhibits excellent rapid charge and discharge characteristics.
[0133] As a method for spheroidizing carbon material raw materials, considering the ease of controlling the particle shape, the method of spheroidizing carbon material raw materials by imparting mechanical energy is preferred.
[0134] Examples of mechanical energy include impact, compression, friction, and shear force. These mechanical energies can be used individually or in combination.
[0135] The method of spherizing carbon raw materials by imparting mechanical energy can be achieved simply by using a device that applies mechanical energy.
[0136] When spheroidizing carbon material raw materials, it is preferable to perform the spheroidizing process while simultaneously adhering the microparticles generated during the spheroidizing process to the surface of the carbon material. By performing the spheroidizing process while simultaneously adhering the microparticles generated during the spheroidizing process to the surface of the carbon material, the porosity within the carbon material can be effectively reduced when coating the carbon material with amorphous carbonaceous materials or graphitic materials. In addition, the amount of edges that can be utilized as lithium ion insertion and extraction sites increases, allowing the electrolyte to be effectively distributed throughout the porosity within the carbon material, resulting in excellent low-temperature input / output characteristics and cycle performance.
[0137] Micronized powder can be produced not only during the spheroidization process, but also by adding micronized powder with adjusted particle size.
[0138] In order to enable the micro powder to adhere effectively to the surface of carbon materials, it is preferable to enhance the adhesion between carbon material particles, between carbon material particles and micro powder particles, and between micro powder particles.
[0139] As a form of adhesion between particles, examples include: van der Waals forces and electrostatic attraction without the aid of interparticle inclusions; and physical cross-linking forces and chemical cross-linking forces with the aid of interparticle inclusions.
[0140] Carbon material raw materials and granulating agents can also be added to the spheroidizing treatment device, and processes (2) and (3) can be carried out simultaneously.
[0141] (Process (4))
[0142] Step (4) is the process of removing the granulating agent.
[0143] Granulators can remove all or part of the material.
[0144] When using granulating agents containing organic solvents, it is preferable to also remove the organic solvents.
[0145] Methods for removing granulating agents and organic solvents include, for example, methods using solvents for cleaning and methods that cause them to evaporate / decompose by heating. Among these methods, the method of causing them to evaporate / decompose by heating is preferred from the perspective of superior productivity and removal efficiency.
[0146] (Process (5))
[0147] Process (5) is the process of pressurizing.
[0148] Examples of pressurization processes include isotropic pressurization and anisotropic pressurization. Among these pressurization processes, isotropic pressurization is preferred from the viewpoint of reducing pore volume.
[0149] Examples of pressurization methods include hydrostatic isotropic pressurization using water as the pressurization medium, gas pressure-based isotropic pressurization using gases such as air as the pressurization medium, and pressurization processes that involve filling a mold and applying pressure in a constant direction through uniaxial pressing.
[0150] The pressure applied is preferably 50 to 300 MPa, more preferably 100 to 280 MPa, and even more preferably 150 to 260 MPa. From the viewpoint of reducing pore volume, the pressure applied is preferably 50 MPa or more, more preferably 100 MPa or more, and even more preferably 150 MPa or more. Furthermore, it is preferably 300 MPa or less, more preferably 280 MPa or less, and even more preferably 260 MPa or less.
[0151] Step (5) can be performed at any point in time between steps (1) and (6), but from the perspective of effectively pressurizing after removing excess granulating agent, it is preferable to perform it between steps (4) and (6).
[0152] (Process (6))
[0153] Process (6) is the process of attaching amorphous carbonaceous material or graphite material.
[0154] By attaching amorphous carbonaceous materials or graphitic materials to carbon materials, side reactions between the negative electrode and the electrolyte can be suppressed, resulting in high capacity and excellent low-temperature input / output characteristics and high-temperature storage characteristics.
[0155] Amorphous carbonaceous materials refer to carbon with a d002 value of 0.340 nm or higher.
[0156] Graphite refers to graphite with a d002 value of less than 0.340 nm.
[0157] As a method for attaching amorphous carbonaceous materials or graphitic materials to carbon materials, from the perspective of easily controlling the amount of voids within the particles, it is preferable to mix the carbon material with an amorphous carbonaceous material precursor or a graphitic material precursor, and heat it in a non-oxidizing atmosphere to carbonize the amorphous carbonaceous material precursor into an amorphous form or to graphitize the graphitic material precursor into a graphitic form.
[0158] Methods for mixing carbon materials with amorphous carbon precursors or graphitic precursors include, for example, using a mixer or kneader to mix the carbon material with the amorphous carbon precursor or graphitic precursor; and adding the carbon material to a solution containing the amorphous carbon precursor or graphitic precursor and removing the solvent. Among these methods, the method of using a mixer or kneader to mix the carbon material with the amorphous carbon precursor or graphitic precursor is preferred from the perspective of effectively reducing micropores of 1 nm to 4 nm.
[0159] The mixing ratio of carbon materials with amorphous carbonaceous precursors or graphitic precursors can be appropriately set to achieve the desired coating rate.
[0160] There are no particular limitations on the atmosphere during heating, as long as it is a non-oxidizing atmosphere. From the perspective of suppressing the formation of micropores caused by oxidation, nitrogen, argon, or carbon dioxide are preferred, and nitrogen is more preferred.
[0161] The oxygen concentration is preferably 1% by volume or less, more preferably 0.1% by volume or less. There is no particular limitation on the lower limit of the oxygen concentration, which is usually 0% by volume or more.
[0162] The heating temperature differs in the amorphous carbonization of amorphous carbonaceous precursors and the graphitization of graphitic precursors.
[0163] The heating temperature for amorphous carbonaceous precursor carbonization is not particularly limited as long as it does not reach a temperature equivalent to the crystal structure of graphite. Preferably, it is 500–2000°C, more preferably 600–1800°C, and even more preferably 700–1600°C. Here, the aforementioned heating temperature is preferably 500°C or higher, more preferably 600°C or higher, and even more preferably 700°C or higher. Furthermore, it is preferably 2000°C or lower, more preferably 1800°C or lower, and even more preferably 1600°C or lower.
[0164] The heating temperature for graphitizing the graphitic precursor is not particularly limited as long as it reaches a temperature equivalent to the crystal structure of graphite. Preferably, it is 2100–3300°C, more preferably 2500–3200°C, and even more preferably 2700–3100°C. Here, the aforementioned heating temperature is preferably 2100°C or higher, more preferably 2500°C or higher, and even more preferably 2700°C or higher. Furthermore, it is preferably 3300°C or lower, more preferably 3200°C or lower, and even more preferably 3100°C or lower.
[0165] The heating time is preferably 0.1 to 1000 hours, more preferably 1 to 100 hours. Here, the heating time is preferably 0.1 hours or more, more preferably 1 hour or more, and further preferably 1000 hours or less, more preferably 100 hours or less.
[0166] Examples of precursors for amorphous carbonaceous materials and graphitic materials include aromatic hydrocarbons such as tar, pitch, naphthalene, and anthracene, as well as thermoplastic resins such as phenolic resins and polyvinyl alcohol resins. These precursors can be used alone or in combination of two or more. Among these precursors, considering the ease of carbon structure development and the ability to achieve minimal coating, tar, pitch, and aromatic hydrocarbons are preferred; substances with a residual carbon content of 50% or more are more preferred; and substances with a residual carbon content of 60% or more are even more preferred.
[0167] The ash content in the amorphous carbonaceous precursor and the graphitic precursor is preferably 0.00001 to 1% by mass in 100% by mass of the amorphous carbonaceous precursor and the graphitic precursor. Here, the ash content is preferably 0.00001% by mass or more in 100% by mass of the amorphous carbonaceous precursor and the graphitic precursor, and is also preferably 1% by mass or less, more preferably 0.5% by mass or less, and even more preferably 0.1% by mass or less.
[0168] For carbon materials obtained through processes (1) to (6), in order to make the volume-based average particle size of the carbon materials reach the desired range, they can be crushed, broken, and graded as needed.
[0169] Crushing, breaking down, and grading can be done using well-known methods.
[0170] (Process (7))
[0171] Process (7) is a process of mixing multiple carbon materials.
[0172] Preferably, the first carbon material and the second carbon material are manufactured separately through the above steps and then mixed. Alternatively, substances other than the first carbon material and the second carbon material may be mixed.
[0173] There are no particular limitations on the mixing method as long as it can produce the desired composition.
[0174] [Negative electrode (solid electrode)]
[0175] In the case of a solid electrode as the negative electrode in this embodiment, it includes a current collector and an active material layer formed on the current collector, the active material layer containing the carbon material (X) of this embodiment. The carbon material of this embodiment has the effect of serving as a negative electrode active material.
[0176] As the negative electrode of the solid electrode, when the mass of the active material layer is set to 100% by mass, it typically contains 0 to 5% by mass of solvent.
[0177] The manufacturing method for the negative electrode of the solid electrode is not particularly limited as long as an active material layer can be formed on the current collector. However, from the perspective of low cost and excellent productivity, it is preferable to coat the current collector with a slurry containing the carbon material and binder resin of this embodiment and then dry it. A thickener may also be added to the slurry.
[0178] Preferably, after the slurry containing the carbon material (X) and the binder resin of this embodiment is applied to the current collector and dried, pressure is applied to increase the density of the active material layer formed on the current collector and increase the battery capacity per unit volume of the active material layer.
[0179] When the negative electrode is a solid electrode, the density of the active material layer is preferably 1.2–2.0 g / cm³. 3 More preferably, it is 1.5–1.8 g / cm³. 3 From the perspective of suppressing the decrease in battery capacity caused by the increase in electrode thickness, the density of the active material layer is preferably 1.2 g / cm³. 3 The above, more preferably 1.5 g / cm³ 3 That's all. Furthermore, considering the reduction in electrolyte volume retained in the gaps due to decreased electrode porosity, reduced mobility of alkaline ions such as lithium ions, and decreased fast charge / discharge characteristics, the density of the active material layer is preferably 2.0 g / cm³. 3 The preferred value is 1.8 g / cm³. 3 the following.
[0180] Furthermore, when the negative electrode is a solid electrode, the thickness of the active material layer is preferably 100–200 μm. The thickness of the active material layer can be measured using a micrometer by peeling the negative electrode active material layer off the current collector.
[0181] When the negative electrode is a solid electrode, the density of the active material layer can be calculated from the mass of the stripped negative electrode active material layer and the volume of the active material layer.
[0182] [Negative electrode (semi-solid electrode)]
[0183] In the case of a semi-solid electrode in this embodiment, the negative electrode includes a current collector, an active material layer formed on the current collector, and an electrolyte. The active material layer contains the carbon material (X) of this embodiment. The carbon material of this embodiment has the effect of serving as a negative electrode active material.
[0184] As the negative electrode of the semi-solid electrode, when the mass of the active material layer is set to 100% by mass, it typically contains 6 to 70% by mass of solvent, preferably 6 to 50% by mass of solvent, and more preferably 6 to 30% by mass of solvent.
[0185] The manufacturing method for the negative electrode of the semi-solid electrode is not particularly limited as long as an active material layer can be formed on the current collector. However, from the perspective of low cost and excellent productivity, the method of coating a slurry containing the carbon material and electrolyte of this embodiment onto the current collector is preferred. A thickener may also be added to the slurry.
[0186] From the perspective of low cost and high productivity, the manufacturing method preferably does not include drying, and more preferably does not include further pressurization.
[0187] When the negative electrode is a semi-solid electrode, the density of the active material layer is preferably 1.0–1.4 g / cm³. 3 .
[0188] Furthermore, when the negative electrode is a semi-solid electrode, the thickness of the active material layer is preferably 201–2000 μm. The thickness of the active material layer can be measured using a contact probe that does not peel the negative electrode active material layer off the current collector.
[0189] When the negative electrode is a semi-solid electrode, the density of the active material layer can be calculated from the mass of the negative electrode active material layer and the volume of the active material layer.
[0190] [Secondary battery]
[0191] The secondary battery of this embodiment includes a positive electrode, a negative electrode of this embodiment, and an electrolyte.
[0192] The positive electrode and the negative electrode in this embodiment are preferably capable of absorbing and releasing lithium ions. The secondary battery can also be a clay-type battery.
[0193] (positive electrode)
[0194] The positive electrode can use a known positive electrode.
[0195] (electrolytes)
[0196] The electrolyte can be a known electrolyte.
[0197] (Diaphragm)
[0198] The secondary battery of this embodiment preferably has a separator sandwiched between the positive and negative electrodes. However, the use of a solid electrolyte as the electrolyte is not excluded in this embodiment.
[0199] The diaphragm can be any known type.
[0200] The carbon material of this embodiment can maintain a high initial efficiency of the secondary battery and suppress the expansion of the electrode plates. Therefore, it is suitable as an active material for the negative electrode of a secondary battery, more suitable as an active material for the negative electrode of a non-aqueous secondary battery, and particularly suitable as an active material for the negative electrode of a lithium-ion secondary battery.
[0201] Example
[0202] The present invention will be specifically described below with examples, but the present invention is not limited to the following examples as long as it does not deviate from its spirit.
[0203] (Volume reference particle sizes d10, d25, d50, and d90, and their frequencies q(d10), q(d25), q(d50), and q) (method for determining d90)
[0204] A 0.01 g sample was suspended in 10 mL of a 0.2% (w / w) aqueous solution of polyoxyethylene sorbitan monolaurate (trade name "Tween20") as a surfactant. The sample was then introduced into a laser diffraction / scattering particle size distribution measuring device (model name "LA-920", manufactured by Horiba Corporation). The sample was irradiated with 28 kHz ultrasound at 60 W output power for 1 minute, followed by measurement. The median particle size of the volume reference in the measuring device was measured, and this median particle size was taken as the volume reference average particle size d50. The particle size distribution data obtained includes the frequency and cumulative frequency corresponding to each particle size. The particle size dn refers to the particle size with a cumulative frequency of n%. The particle size dn is calculated by linear interpolation from the two closest data points (n1%, dn1) and (n2%, dn2) sandwiching the cumulative frequency n%.
[0205] Similarly, the frequency q(dn) at dn is also calculated by linear interpolation from the data of the two closest points sandwiching dn.
[0206] (Measurement of tap density)
[0207] The tap density was measured using a tapped density measuring device (model name "GeoPyc1365", manufactured by Micromeritics) via compression. The density at which a compressive force of 108 N was applied was taken as the tapped density.
[0208] (Methods for determining specific surface area (SA))
[0209] Using a specific surface area measuring device (model name "Macsorb HM-1210", manufactured by Mounttech Co., Ltd.), the sample was pre-dryed under reduced pressure at 350°C for 15 minutes under nitrogen flow, then cooled to liquid nitrogen temperature. The specific surface area was determined by the nitrogen adsorption BET one-point method using a nitrogen-helium mixed gas with the relative pressure of nitrogen to atmospheric pressure precisely adjusted to 0.3.
[0210] (Method for determining the oil absorption of flaxseed oil)
[0211] The oil absorption of flaxseed oil was determined according to ISO 4546.
[0212] Specifically, using an oil absorption measuring device (model name "S410D", developed by Asahi Shimbun Co., Ltd.), 30g of sample was added, and the measurement was conducted under the conditions of a flaxseed oil dripping rate of 4mL / min and a rotation speed of 200rpm. The amount of oil absorbed was defined as the amount added when the torque reached 70% of the maximum torque.
[0213] (Making of negative electrode plates)
[0214] Using the carbon materials obtained in the examples and comparative examples as the negative electrode active material, an electrode plate with an active material layer having an active material layer density of 1.50 ± 0.03 g / cm³ was fabricated. Specifically, 50.00 ± 0.02 g of a 1% (w / w) sodium carboxymethyl cellulose aqueous solution (equivalent to 0.50 g of solids) and 1.00 ± 0.05 g of a styrene-butadiene rubber aqueous dispersion with a weight average molecular weight of 270,000 (equivalent to 0.50 g of solids) were added to 50.00 ± 0.02 g of the carbon material obtained in the examples and comparative examples. The mixture was stirred for 5 minutes using a hybrid mixer (manufactured by Keyence Corporation) and degassed for 30 seconds to obtain a slurry.
[0215] The obtained slurry was coated using a die-casting machine with an anode material adhesion amount of 10.00 ± 0.30 mg / cm². 2The active material layer was coated onto a 10μm thick copper foil, 5cm wide, to serve as the current collector. After drying, it was rolled using a 20cm diameter roller to adjust the density of the active material layer to 1.50±0.03g / cm³. 3 The negative electrode sheet is obtained. The load during the rolling process is used as the pressing load.
[0216] (Making of button batteries)
[0217] The obtained negative electrode sheet was punched into a disc shape with a diameter of 12.5 mm to serve as the negative electrode, and the lithium metal foil was punched into a circular plate shape with a diameter of 14 mm to serve as the counter electrode. A separator (made of porous polyethylene membrane) impregnated with electrolyte was placed between the two electrodes. The electrolyte was prepared by dissolving LiPF6 in a mixed solvent of ethylene carbonate and ethyl methyl carbonate (volume ratio 30:70) at 1 mol / L and adding 2% by mass of ethylene carbonate. A 2032 button cell was fabricated as a secondary battery.
[0218] (Methods for determining the irreversible capacity and initial efficiency of the negative electrode of a secondary battery)
[0219] The resulting button cell was charged to 5mV relative to the lithium counter electrode at a current density of 0.04C, and then charged to a current density of 0.004C at a constant voltage of 5mV. After lithium doping to the negative electrode, it was discharged to 1.5V relative to the lithium counter electrode at a current density of 0.08C. The difference between the charging capacity and the discharging capacity at this point was taken as the irreversible capacity, and the ratio of the discharging capacity to the charging capacity ((discharging capacity / charging capacity) × 100) was taken as the initial efficiency (%).
[0220] [Example 1]
[0221] Flake-shaped natural graphite with an average particle size (d50) of 100 μm was pulverized to obtain flake-shaped natural graphite with a d50 of 26 μm. 12 parts by mass of liquid oil were mixed into 100 parts by mass of the obtained flake-shaped natural graphite as a granulating agent, followed by spheroidization treatment. The granulating agent was further removed by heat treatment to obtain spheroidized natural graphite. The obtained spheroidized natural graphite was filled / sealed in a rubber container and subjected to isotropic pressure treatment at 200 MPa. The resulting molded product was then crushed / graded. The obtained spheroidized natural graphite powder was mixed with asphalt, a precursor for amorphous carbon, adjusted to 0.02% by mass ash, 20 ppm by mass metal impurities, and 1% by mass Qi. The furnace pressure was reduced to below 10 torr, and nitrogen was introduced to repressurize to atmospheric pressure. Nitrogen was then introduced again to reduce the oxygen concentration in the furnace to less than 100 ppm. Heat treatment was then performed at 1300°C in an inert gas environment. By crushing / grading the obtained sintered material, a carbon material with a d50 of 27.5 μm and containing amorphous carbonaceous matter on the surface of graphite particles is obtained.
[0222] The sintering yield confirmed that the mass ratio of spherical graphite particles to amorphous carbonaceous matter (spherical graphite particles: amorphous carbonaceous matter) in the obtained carbon material (composite carbon material) was 1:0.11. The obtained carbon material had a d10 of 15.57 μm and a q(d10) of 3.63%, a d25 of 20.93 μm and a q(d25) of 8.29%, a d50 of 27.9 μm and a q(d50) of 12.61%, and a d90 of 48.11 μm and a q(d90) of 6.48%. For the obtained carbon material, the tap density, oil absorption, specific surface area, compression load, initial efficiency, and capacity were determined using the methods described above. The results are shown in Tables 1 and 2.
[0223] [Example 2]
[0224] Spheroidized natural graphite with a d50 of 7.4 μm was filled into a rubber container and sealed. After isotropic pressurization at 200 MPa, the resulting molded material was crushed / graded. The obtained spheroidized natural graphite powder was mixed with asphalt (a precursor for amorphous carbon) at 100 wt%, with the asphalt adjusted to 0.02 wt% ash, 20 wt% metallic impurities, and 1 wt% Qi. The furnace pressure was reduced to below 10 torr, then nitrogen was introduced to repressurize to atmospheric pressure, followed by nitrogen to reduce the oxygen concentration in the furnace to less than 100 ppm. Heat treatment was then performed at 1300 °C in an inert gas environment. By crushing / grading the resulting calcined material, a composite carbon material with a d50 of 9.0 μm and amorphous carbonaceous material on the surface of the graphite particles was obtained. The firing yield confirmed that the mass ratio of spherical graphite particles to amorphous carbon matter in the obtained composite carbon material was 1:0.11. The obtained carbon material was mixed with the carbon material with a d50 of 27.5 μm obtained in Example 1 at a mass ratio of 2:8 to obtain the carbon material.
[0225] The obtained carbon material has a d10 of 7.98 μm and a q(d10) of 2.59%, a d25 of 14.89 μm and a q(d25) of 4.01%, a d50 of 24.73 μm and a q(d50) of 8.52%, and a d90 of 47.24 μm and a q(d90) of 5.86%. The evaluation results of the obtained carbon material are shown in Tables 1 and 2.
[0226] [Example 3]
[0227] Except that the carbon material obtained in Example 2 and the carbon material with a d50 of 27.5 μm obtained in Example 1 were set at a mass ratio of 3:7, the carbon material was obtained in the same manner as in Example 2.
[0228] The obtained carbon material has a d10 of 6.62 μm and a q(d10) of 3.30%, a d25 of 11.19 μm and a q(d25) of 3.97%, a d50 of 21.92 μm and a q(d50) of 6.45%, and a d90 of 46.81 μm and a q(d90) of 5.17%. The evaluation results of the obtained carbon material are shown in Table 1.
[0229] [Comparative Example 1]
[0230] Except for pulverizing flake natural graphite with an average particle size (d50) of 100 μm to obtain flake natural graphite with a d50 of 11 μm, the same procedure as in Example 1 was followed to obtain a negative electrode material with a d50 of 16.6 μm.
[0231] The obtained carbon material has a d10 of 9.91 μm and a q(d10) of 4.38%, a d25 of 12.69 μm and a q(d25) of 9.44%, a d50 of 16.58 μm and a q(d50) of 13.17%, and a d90 of 29.47 μm and a q(d90) of 5.75%. The evaluation results of the obtained anode material are shown in Tables 1 and 2.
[0232] [Comparative Example 2]
[0233] Except for setting the mass ratio of spherical graphite particles to amorphous carbonaceous matter (spherical graphite particles: amorphous carbonaceous matter) to 1:0.12, the same procedure as in Comparative Example 1 was followed to obtain an anode material with a d50 of 16.9 μm.
[0234] The obtained carbon material has a d10 of 10.44 μm and a q(d10) of 4.58%, a d25 of 13.21 μm and a q(d25) of 10.09%, a d50 of 16.89 μm and a q(d50) of 14.32%, and a d90 of 28.07 μm and a q(d90) of 7.02%. The evaluation results of the obtained anode material are shown in Tables 1 and 2.
[0235]
[0236] The carbon materials in Examples 1-3 exhibit reduced pressing loads, resulting in decreased irreversible capacity and excellent initial efficiency even with the same powder SA. Adjusting the content of amorphous carbonaceous material and the heating temperature brought the true density and Raman R value within specified ranges, thus suppressing the irreversible capacity of the negative electrode and achieving excellent initial efficiency.
[0237] On the other hand, the carbon materials in Comparative Examples 1 and 2 have a large pressing load, which increases the irreversible capacity of the negative electrode and results in poor initial efficiency of the negative electrode.
[0238] Those skilled in the art will obviously conceive of various modifications or alterations within the scope of the claims, and it should be understood that these also fall within the technical scope of this invention. Furthermore, the constituent elements of the above embodiments can be combined arbitrarily without departing from the spirit of the invention.
[0239] It should be noted that this application is based on Japanese patent application filed on March 29, 2024 (Japanese Patent Application No. 2024-057421), the contents of which are incorporated herein by reference.
Claims
1. A carbon material, wherein, Flaxseed oil has an oil absorption rate of less than 40.0 mL / 100g. The frequency q (d50) below the particle size at which the cumulative volume ratio in the particle size distribution of the volume reference is 50% is also called d50, which is below 13.0%.
2. The carbon material according to claim 1, wherein, The carbon material comprises a first carbon material and a second carbon material with different d50 values. The d50 of the first carbon material is greater than 25 μm.
3. The carbon material according to claim 1, wherein, The carbon material comprises a first carbon material and a second carbon material with different d50 values. The d50 of the second carbon material is less than 15 μm.
4. The carbon material according to any one of claims 1 to 3, wherein, The carbon material is graphite coated with an amorphous material.
5. The carbon material according to any one of claims 1 to 3, wherein, The particle size below the cumulative volume ratio of the carbon material when it is 90% is also referred to as the difference between d90 and d50, that is, d90-d50 is 13.0 μm or more.
6. The carbon material according to any one of claims 1 to 3, wherein, The difference between the d50 and the particle size below the cumulative volume ratio of the carbon material (also referred to as d10), i.e., d50-d10 is 7.0 μm or more.
7. The carbon material according to any one of claims 1 to 3, wherein, The difference between d90 and d10 of the carbon material, i.e., d90-d10, is greater than 20 μm.
8. The carbon material according to any one of claims 1 to 3, wherein, The ratio of the difference between d90 and d10 of the carbon material to d50, i.e., (d90-d10) / d50, is greater than 1.
05.
9. The carbon material according to any one of claims 1 to 3, wherein, The ratio of the frequency q(d50) of d50 in the volume-based particle size distribution of the carbon material to the frequency q(d25) of d25 (also known as the particle size at which the cumulative volume ratio in the volume-based particle size distribution is 25%), i.e., q(d50) / q(d25), is 3.5 or less.
10. The carbon material according to any one of claims 1 to 3, wherein, The ratio of the frequency q(d50) of d50 in the volumetric particle size distribution of the carbon material to the frequency q(d90) of d90 in the volumetric particle size distribution, i.e., q(d50) / q(d90), is less than 2.
0.
11. The carbon material according to any one of claims 1 to 3, wherein, The frequency q(d25) of d25 in the volume-based particle size distribution of the carbon material is below 9.0%.
12. The carbon material according to any one of claims 1 to 3, wherein, The ratio of the frequency q(d90) of d90 in the volumetric particle size distribution of the carbon material to the frequency q(d10) of d10 in the volumetric particle size distribution, i.e., q(d90) / q(d10), is 1.55 or higher.
13. A negative electrode comprising a current collector and an active material layer formed on the current collector, the active material layer comprising a carbon material according to any one of claims 1 to 3.
14. A secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, wherein the negative electrode is a negative electrode comprising a carbon material according to any one of claims 1 to 3.
Citation Information
Patent Citations
Negative electrode material for nonaqueous secondary battery, negative electrode for nonaqueous secondary battery, and nonaqueous secondary battery
JP2021158043A
Negative electrode material raw material for nonaqueous secondary battery, negative electrode material for nonaqueous secondary battery, negative electrode for nonaqueous secondary battery, and nonaqueous secondary battery
JP2021158044A
Film electrode bonded body
JP2024057421A
